Effect of a participatory organizational-level occupational health intervention on short-term sickness absence: a cluster randomized controlled trial - Framke, Elisabeth; Sørensen, Ole Henning; Pedersen, Jacob; Rugulies, Reiner (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'The aim of this study was to examine whether employees in pre-schools that implemented a participatory organizational-level intervention focusing on the core task at work had a lower incidence of short-term sickness absence compared to employees in the control group. ' ' METHODS ': 'The cluster randomized controlled trial (RCT) comprised 78 pre-schools that were allocated to the intervention (44 pre-schools with 1760 employees) or control (34 pre-schools with 1279 employees) group. The intervention lasted 25 months and followed a stepwise and structured approach, consisting of seminars, workshops, and workplace-directed intervention activities focusing on the core task at work. Using Poisson regression, we tested differences in incidence rates in short-term sickness absence between the intervention and control groups during a 29-months follow-up. ' ' RESULTS ': 'Estimated short-term sickness absence days per person-year during follow-up were 8.68 and 9.17 in the intervention and control groups, respectively. The rate ratio (RR) for comparing incident sickness absence in the intervention to control groups during follow-up was 0.93 [95% confidence interval (95% CI) 0.86–1.00] in the crude analysis and 0.89 (95% CI 0.83–0.96) when adjusting for age, sex, job group, type and size of workplace, and workplace average level of previous short-term sickness absence. A supplementary analysis showed that the intervention also was associated with a reduced risk of long-term sickness absence with a crude RR of 0.83 (95% CI 0.69–0.99) and an adjusted RR of 0.84 (95% CI 0.69–1.01). ' ' CONCLUSIONS ': 'Pre-school employees participating in an organizational-level occupational health intervention focusing on the core task at work had a lower incidence of short-term sickness absence during a 29-month follow-up compared with control group employees.
Keywords: cluster randomized controlled trial; core task; intervention; occupational health; psychosocial; randomized controlled trial; RCT; short-term sickness absence; sickness absence; stress; stress-as-offense-to-self